Evaluation Of The Radiation Dose For Mammography In King Hussein Cancer Center, Jordan - Hegian, Zeinab Ahmed Shaker (2023)
Breast cancer is the most typical kind of cancer among women. Meanwhile, mammography is the most widely used and effective diagnostic technique for early detection of breast cancer. Since breast tissue is particularly sensitive to radiation, the mean glandular dose (MGD) is determined by utilizing several of the breast screening-specific exposure radiation dose criteria. The patient can receive the least amount of radiation possible with an image quality that allows for the visibility of pathological findings. As a result, the Diagnostic Reference Level (DRL) was established in order to provide optimum exposure parameters for assessing and reducing patient radiation doses. Since no data on mammography radiation doses exists in Jordan, this study focuses on preparing a preliminary set of data by analysing patient dose, average glandular dose, and DRL within nine mammogram units. The study comprised of 3600 data for patients aged 21 to 80 years old with a Compressed Breast Thickness (CBT) of 16.9 mm to 156 mm. Finally, patient radiation dose data was compared to other published studies in the literature. The DRLs for the entire sample were calculated using the 75th and 95th percentiles of the MGD variable. The DRL values in Jordan at the 75th and 95th percentiles are 2.03 mGy and 2.93 mGy, respectively. Following that, the DRLs values for four different projections ((right craniocaudal (RCC) view, left craniocaudal (LCC) view, right mediolateral oblique (RMLO) view, and left mediolateral oblique (LMLO) view) are established in this study